Provision of Indonesian Preschool Gymnastics to Children to Improve Physical Fitness - tsanyan dary mahdy; dary, tsanyan; irwan, irwan; maihendra anggara, liyant; zidane alfareza, daffa; nuari panggraita, gilang (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2023)
The purpose of the SPI exercise training is to improve physical fitness.The method of implementing this activity was carried out by mutual agreement with the team from SD 2 Karyomukti based on a request from the madrasah. The service for SD 2 Karyomukti children is located in Karyomukti Village, Kesesi District. There are 5 Karyomukti Elementary School 2 students who will take part in the SPI gymnastics service program. This training activity was given 1 meeting. Training is held on Monday at 10.00 WIB until finished. SD 2 Karyomukti field area. The training method used to conduct training is by practicing SPI gymnastics. The output results achieved in this activity are: (1) SD 2 Karyomukti students have better physical fitness. (2) Knowing the science of sports, especially SPI gymnastics besides the religious knowledge studied, has spiritual and physical health.